Thermodynamic studies of (RbF + RbCl + H2O) and (CsF + CsCl + H2O) ternary systems from potentiometric measurements at T = 298.2 K. (December 2016) - Huang, Xiaoting; Li, Shu'ni; Zhai, Quanguo; Jiang, Yucheng; Hu, Mancheng
Graphical abstract: Thermodynamic properties, such as mean activity coefficients, osmotic coefficients and excess Gibbs free energies, of the RbF + RbCl + H2 O and CsF + CsCl + H2 O ternary systems were determined from potentiometric measurement at 298.2 K. The Pitzer model and the Harned rule were used to fit the experimental data. Highlights: Thermodynamic properties of RbF + RbCl + H2 O and CsF + CsCl + H2 O ternary systems were determined. The Pitzer model and the Harned rule were used to correlate the experimental data. The mean activity coefficients, osmotic coefficients, and the excess Gibbs free energy were also obtained. Abstract: Thermodynamic properties of (RbF + RbCl + H2 O) and (CsF + CsCl + H2 O) systems were determined by the potentiometric method for different ionic strength fractions y B of RbCl/CsCl at 298.2 K. The Pitzer model and the Harned rule were used to fit the experimental values. The Pitzer mixing parameters and the Harned coefficients were evaluated. In addition, the mean ionic activity coefficients of RbF/CsF and RbCl/CsCl, the osmotic coefficients, and the excess Gibbs energies of the systems studied were calculated.